Dynamic modeling and endurance enhancement analysis of deep-sea gliders with a hybrid buoyancy regulating system. (1st December 2020) - Zhou, Hexiong; Fu, Jian; Liu, Chunhu; Zeng, Zheng; Yu, Caoyang; Yao, Baoheng; Lian, Lian
Abstract: Buoyancy loss caused by hull deformation and seawater density variation presents key challenges for underwater gliders operating in deep-sea environments. This paper proposes a hybrid buoyancy regulating system (HBRS) based on energy accumulator for deep-sea gliders (DGs), which can effectively utilize the ocean pressure differential energy to realize buoyancy compensation. The proposed mathematical model of DG with HBRS is established by means of the Newton–Euler formalism and Boyier law, revealing the relationship between the buoyancy of DG and depth. The motion characteristics of DG with HBRS in zigzag and spiraling operating pattern are fully analyzed by comparisons among DG operating in ideal environment and more practical environment considering buoyancy loss, which shows that the HBRS facilitates a deeper diving depth and a more stable gliding attitude for DG. Energy consumption analysis is carried out by disassembling a profile into descent and ascent process and the results indicate that the employed HBRS is beneficial for energy saving, particularly in the process of the floating motion of DG. Moreover, a novel oil draining strategy is proposed to further reduce energy consumption of DG with HBRS. The results of various simulations and experiments validate effective improvement in operating efficiency and energy saving of the presented system. Highlights: A HBRS is proposed for deep-sea gliders to utilize pressure differential energy. A full model for gliders with HBRS is established considering the buoyancy variation. The motion performance improvement and energy saving are analyzed and verified. A novel oil draining strategy is proposed to further reduce the energy consumption.